STUDENTS’ LEARNING MOTIVATION THROUGH EDMODO: BLENDED LEARNING IN ESP CLASSROOM - Merie Agustiani; Sulia Ningsih; Anggraeni Agustin Muris (Research and Development Journal of Education, 2021)
The advent of technology requires educators to bring technology into the classroom to involve the students as digital-native. Without having a motivation, a student or even a teacher or reader is unable to reach the learning objectives. Virtual worlds are believed to become creative complementary tools to inspire and enable the students to learn independently.  They are widely used and blended with face-to-face learning in the teaching and learning process. This study focused on how Edmodo could raise students’ motivation. This descriptive study involved forty-four students of Education Technology Study Program of Baturaja University who took the English course in the second semester of academic year 2019/2020. The data were collected through a questionnaire with twenty questions and analyzed by using descriptive statistics. The result showed that students were instrumentally motivated in learning English and students’ performance goal was higher than their learning goal even though there was no significant difference between the performance and learning goals.